Preservatives for rapid growth timber - A review - Dias, Kelly Bossardi [UNESP]; Barreiros, Ricardo Marques [UNESP] (My University, 2018)
The shortage of species that are resistant to biological deterioration has forced man to use less durable, mainly fast-growing, reforestations, such as some species of Eucalyptus and Pinus. These species have moderate or no resistance to the attack of biological agents and require condoms. The decomposition of wood and other cellulosic materials by fungi causes significant economic loss. Until recently, the most widely used wood preservative was chromium copper arsenate (CCA). However, the use of CCA in the treatment of wood has been banned for more than a decade because of issues raised regarding the environmental impact and safety of arsenic and chromium. As CCA replacements, arsenic-free and chrome-free wood preservatives are sought. Thus, the aim of research has been to develop environmentally correct and effective products against the attack of biodeteriorating agents. This article reviews the alternatives you have searched for. The search for alternatives to current condoms has been efficient, but not effective, that is, a viable alternative to existing products has not yet been found. Based on several studies, the demand for a preservative for wood can be divided into extractives of plants and by-products of processes.
Preservantes para madeiras de rápido crescimento – Uma revisão
Keywords: Biodeterioration; By-products; Extractives